Microbiome Management: Transitioning from Chemical Inputs to Biological Soil Fertility for Sustainable Agriculture - Diksha Vishwakarma; Shashi S Yadav; Subhash Chandra Gupta (Public Health, 2026)
The growing concern over declining soil health under intensive agricultural systems has necessitated a shift toward biologically driven fertility management approaches. Excessive reliance on synthetic fertilizers has been associated with nutrient imbalances, reduced microbial diversity, and environmental degradation. Recent research highlights the soil microbiome as a critical determinant of nutrient cycling and plant productivity. Microorganisms such as bacteria, fungi, and archaea regulate key processes including nitrogen fixation, phosphorus solubilization, and organic matter decomposition. This review synthesizes findings from recent empirical studies to evaluate the role of microbiome management in enhancing soil fertility. Evidence suggests that integrating microbial inoculants, organic amendments, and precision microbiome interventions can improve nutrient use efficiency and crop yield. However, variability in field performance and limited understanding of microbial interactions remain major challenges. The review concludes that microbiome-based strategies provide a viable pathway for sustainable agriculture, but require further refinement for large-scale application.